ChemInform Abstract: Direct Oxidative Arylation of Aryl C—H Bonds with Aryl Boronic Acids via Pd Catalysis Directed by the N, N‐Dimethylaminomethyl Group. Issue 47 (November 2015) - Zhang, Ji‐Cheng; Shi, Jiang‐Ling; Wang, Bi‐Qin; Hu, Ping; Zhao, Ke‐Qing; Shi, Zhang‐Jie
Abstract: Various benzylamines are highly efficiently and highly regioselectively ortho‐arylated leading to mono‐ or diarylated arenes under mild reaction conditions.